2018
DOI: 10.1038/s41598-018-24831-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in gene expression in chronic allergy mouse model exposed to natural environmental PM2.5-rich ambient air pollution

Abstract: Particulate matter (PM) air pollution has been associated with an increase in the incidence of chronic allergic diseases; however, the mechanisms underlying the effect of exposure to natural ambient air pollution in chronic allergic diseases have not been fully elucidated. In the present study, we aimed to investigate the cellular responses induced by exposure to natural ambient air pollution, employing a mouse model of chronic allergy. The results indicated that exposure to ambient air pollution significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
(43 reference statements)
1
11
0
Order By: Relevance
“…creased AR mobidity. 2 Indeed, recent studies from China have demonstrated that the concentrations of particulate matter <2.5 μm (PM2.5) and PM10 in the air were closely related to the incidence of AR, 3,4 and additionally significantly impacted the type and concentration of pollen. 5 Evidence indicates that nasal epithelial cells play an integral role in innate and adaptive immune responses to diverse environmental pollutants and allergens by synthesizing and releasing numerous inflammatory cytokines.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…creased AR mobidity. 2 Indeed, recent studies from China have demonstrated that the concentrations of particulate matter <2.5 μm (PM2.5) and PM10 in the air were closely related to the incidence of AR, 3,4 and additionally significantly impacted the type and concentration of pollen. 5 Evidence indicates that nasal epithelial cells play an integral role in innate and adaptive immune responses to diverse environmental pollutants and allergens by synthesizing and releasing numerous inflammatory cytokines.…”
mentioning
confidence: 99%
“…The prevalence of AR has markedly increased during the past 30 years, especially in developing countries, with increasing evidence showing that air pollution is likely to be associated with increased AR mobidity 2 . Indeed, recent studies from China have demonstrated that the concentrations of particulate matter <2.5 µm (PM2.5) and PM10 in the air were closely related to the incidence of AR, 3,4 and additionally significantly impacted the type and concentration of pollen 5 …”
mentioning
confidence: 99%
“…Furthermore, excessive ROS in the lung tissue would activate neutrophils, which resulted in continuous airway inflammatory reactions. Studies indicated that PM 2.5 would cause cell infiltration and structural remodeling [20]. And in this study, we observed the cells response to amyloid-beta after PM 2.5 exposure, which was reported to promote fiber deposition [47].…”
Section: Idmentioning
confidence: 75%
“…Several studies have suggested that the alternation of gene expression played a major role in the activation of pathways induced by toxicant exposure [20][21][22][23][24]. Recent studies indicated that PM 2.5 could enter cells via pinocytosis, and could alter the gene expression of lung epithelial and myocardial cells.…”
mentioning
confidence: 99%
“…For ethical reasons, it is impossible to perform in vivo provocations with PM in humans, and most studies on its mechanism of action are performed in mice [10]. The basophil activation test (BAT) is an in vitro specific provocation test, which can replace potentially dangerous in vivo provocations [11].…”
Section: Introductionmentioning
confidence: 99%